Diking‐induced moderate‐magnitude earthquakes on a youthful rift border fault: The 2002 Nyiragongo‐Kalehe sequence, D.R. Congo. (21st December 2015) - Wauthier, C.; Smets, B.; Keir, D.
Abstract: On 24 October 2002, Mw 6.2 earthquake occurred in the central part of the Lake Kivu basin, Western Branch of the East African Rift. This is the largest event recorded in the Lake Kivu area since 1900. An integrated analysis of radar interferometry (InSAR), seismic and geological data, demonstrates that the earthquake occurred due to normal‐slip motion on a major preexisting east‐dipping rift border fault. A Coulomb stress analysis suggests that diking events, such as the January 2002 dike intrusion, could promote faulting on the western border faults of the rift in the central part of Lake Kivu. We thus interpret that dike‐induced stress changes can cause moderate to large‐magnitude earthquakes on major border faults during continental rifting. Continental extension processes appear complex in the Lake Kivu basin, requiring the use of a hybrid model of strain accommodation and partitioning in the East African Rift. Key Points: Mw 6.2 earthquake due to normal slip on a major preexisting east‐dipping rift border fault Diking could promote faulting on border faults of the rift in the central part of Lake Kivu Diking plays a major role in accommodating upper crustal extension in a considered magma‐poor rift